The role of expectations in the inflation process in the euro area - Maritta Paloviita; Matti Virén (Bank of Finland, 2005)
This paper analyses the role of inflation expectations in the euro area. On one hand, the question is how inflation expectations affect both inflation and output,and, on the other hand, how inflation expectations reflect developments in these variables. The analyses make use of a simple VAR model of inflation, inflation expectations and the output gap that allows for an analysis of the dynamic interrelationship between these variables. This model is estimated on aggregate euro area data, pooled euro area country data and individual country data for the period 1979–2003. The empirical results give strong support for the idea that inflation expectations are the key ingredient of the inflationary process for the whole euro area and for most individual countries as well. Inflation expectations also have a significant negative impact on output. As for the determination of inflation expectations, it turns out that they are relatively persistent, almost as persistent as output. Even so, and especially in the medium term, inflation expectations adapt to developments in both output and (actual) inflation.
URN:NBN:fi:bof-201501281019
Keywords: E31; E52; 330; inflation; expectations; monetary policy; Phillips curve